(untitled) (Economic and Political Thought, 2023)
The trade war between the United States and China, initiated in 2018, has destabilized global trade and economy. Despite the signing of the so-called Phase One Agreement in January 2020, the effects of this economic confrontation extend far beyond its immediate consequences. This article reviews the early consequences of the trade war, drawing on analyses from available sources, taking into account the latest events and data to assess the conflict’s impact on the global economy. Particular attention is paid to recent changes in the trade policies of both countries and their impact on global supply chains and economic outcomes, emphasizing the long-term implications for the global trade order and economic growth.